1991
DOI: 10.1111/j.1471-4159.1991.tb02579.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intracellular Calcium in Cerebellar Granule Neurons: Effects of Depolarization and of Glutamatergic and Cholinergic Stimulation

Abstract: The regulation of the cytosolic free Ca2+ concentration ([Ca2+]i) was investigated by microfluorimetry in single cerebellar granule neurons exposed to various treatments (high K+, glutamate, or acetylcholine) and drugs. The responses to the treatments developed asynchronously during cell culture, with high K+ and glutamate reaching their maxima at 6 and 7 days in vitro and acetylcholine at 9 days in vitro. The biphasic [Ca2+]i transients induced by high K+ (an initial peak, followed by a plateau 30-40% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
29
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 32 publications
9
29
0
Order By: Relevance
“…With intracellular recordings of striatal neurons, microiontophoretic applications of NMDA initiates spiking within a few hundred milliseconds of ejection current onset, and this is followed by a depolarization plateau upon which spikes with a decreased amplitude occur (Herrling et al, 1983;Cepeda et al, 1991). The initial burst of action potentials is likely mediated by Na ϩ and the longer lasting (several seconds) depolarized plateau is dependent on Ca 2ϩ currents (Herrling et al, 1983;Lambert et al, 1989;Cepeda et al, 1991;Ciardo and Meldolesi, 1991). In the present study, an apparent depolarization blockade was also observed with AMPA.…”
Section: Da Depletion Enhances Effects Of Nmda In Vp 379supporting
confidence: 69%
See 1 more Smart Citation
“…With intracellular recordings of striatal neurons, microiontophoretic applications of NMDA initiates spiking within a few hundred milliseconds of ejection current onset, and this is followed by a depolarization plateau upon which spikes with a decreased amplitude occur (Herrling et al, 1983;Cepeda et al, 1991). The initial burst of action potentials is likely mediated by Na ϩ and the longer lasting (several seconds) depolarized plateau is dependent on Ca 2ϩ currents (Herrling et al, 1983;Lambert et al, 1989;Cepeda et al, 1991;Ciardo and Meldolesi, 1991). In the present study, an apparent depolarization blockade was also observed with AMPA.…”
Section: Da Depletion Enhances Effects Of Nmda In Vp 379supporting
confidence: 69%
“…at ASPET Journals on May 12, 2018 jpet.aspetjournals.org inactivation induced acutely by EAA are not yet known, but alterations in Na ϩ and/or Ca 2ϩ conductance are likely candidates (Herrling et al, 1983;Lambert et al, 1989;Cepeda et al, 1991;Ciardo and Meldolesi, 1991). With intracellular recordings of striatal neurons, microiontophoretic applications of NMDA initiates spiking within a few hundred milliseconds of ejection current onset, and this is followed by a depolarization plateau upon which spikes with a decreased amplitude occur (Herrling et al, 1983;Cepeda et al, 1991).…”
Section: Da Depletion Enhances Effects Of Nmda In Vp 379mentioning
confidence: 99%
“…Cerebellar granule cells possess a variety of receptors coupled to Ins(1,4,5)P3 generation, Ins(1,4,5)P3 receptors and the potential for second messenger-induced Ca2 + release from intracellular stores. It would seem probable therefore that the ability of 'metabotropic' excitatory amino acid, and perhaps muscarinic, agonists to release Ca2+ from intracellular stores of granule cells (Courtney et al, 1990;Irving et al, 1990;Ciardo & Meldolesi, 1991) involves this signalling sequence. The precise role(s) of Ins(1,4,5)P3-stimulated changes in intracellular Ca2+ concentration in excitable tissues is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies on the mecha nism of neuronal death suggest that ischemia/hypoxia induced neuronal death is due to the release of glutamate (Glu) from brain tissue during hypoxia, and the excessive extracellular accumulation of Glu results in a Ca 21 over load which leads to neuronal degeneration (3 5). For these reasons, the direct effects of calcium antagonists which block the VOC and/or receptor operated calcium channel (ROC) may be beneficial and expected to improve the neuronal dysfunction either by blocking [Ca 21]i in crease or modulating Glu release (6).…”
mentioning
confidence: 99%